The Development of Mechanical Allodynia in Diabetic Rats Revealed by Single-Cell RNA-Seq - Zhou, Han; Yang, Xiaosheng; Liao, Chenlong; Chen, Hongjin; Wu, Yiwei; Xie, Binran; Ma, Fukai; Zhang, WenChuan (Frontiers in Molecular Neuroscience, 2022)
Mechanical allodynia (MA) is the main reason that diabetic peripheral neuropathy (DPN) patients seek medical advice, which severely debilitates the quality of life. Investigating hyperglycemia-induced changes in neural transcription could provide fundamental insights into the complex pathogenesis of painful DPN (PDPN). Gene expression profiles of physiological dorsal root ganglia (DRG) have been studied. However, the transcriptomic changes in DRG neurons in PDPN remains largely unexplored. In this study, by single-cell RNA sequencing on dissociated rat DRG, we identified five physiological neuron types and a novel neuron type MAAC (Fxyd7+/Atp1b1+) in PDPN. The novel neuron type originated from peptidergic neuron cluster and was characterized by highly expressing genes related to neurofilament and cytoskeleton. Based on the inferred gene regulatory networks, we found that activated transcription factors Hobx7 and Larp1 in MAAC could enhance Atp1b1 expression. Moreover, we constructed the cellular communication network of MAAC and revealed its receptor-ligand pairs for transmitting signals with other cells. Our molecular investigation at single cell resolution advances the understanding of the dynamic peripheral neuron changes and underlying molecular mechanisms during the development of PDPN.